Chia ( Salvia hispanica L.) current situation and future trends - Xingú López, Andrés; González Huerta, Andrés; de La Cruz Torres, Eulogio; Sangerman Jarquín, Dora María; Orozco de Rosas, Guillermo; Rubí Arriaga, Martin (Revista Mexicana de Ciencias Agrícolas, 2017)
The chia is a grain appreciated for its high content of fatty acids, including omega 3 useful for counteracting triglycerides, similarly it is related to weight loss in humans, in pre-hispanic times was required as payment of tribute to the conquering peoples, their seeds were used as a revitalizer for combatants who went to war, and for women who were preparing for childbirth, their use today is common in the preparation of fresh water, in preparation of oil, and as an enricher of baked goods. Its production was lost as a result of the conquest as the Spanish brought new crops, which displaced that of the Chia, condemning it to plant only in very remote areas. Currently the cultivation of chia has had a rebound thanks to its properties, which have allowed to expand its consumption. As México is a place of origin, there are conditions that are conducive to the development of the crop, only the best places and the appropriate practices must be sought to be successful in the development of the crop. Taking into account the above, a bibliographic review was carried out, the objective of this work being to present future and current trends of chia.
Keywords: Salvia hispanica L.; alternative production; nutritional properties